He Role of Wrestling Sports (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article tells about the struggle for our national values, its history, the role and significance of sport, especially wrestling, in the upbringing of a harmoniously developed generation. At the same time, information was analyzed about many famous wrestlers who grew up in our country, about the reforms carried out in our country in the field of sports.